The population of airborne microorganisms and the presence of Staphylococcus aureus in cattle farm at Ladang Pasir Akar - Azman, Azid; Fathurrahman, Lananan; Nur Syuhada, Ahmad Nordin (Penerbit Universiti Sultan Zainal Abidin, 2020)
Microorganisms found in bio aerosols from animals’ confinement buildings is not only foster the risk of spreading diseases among livestock itself, but also pose health hazard among farm workers and nearby residents. The objectives of this study are to observe the population of microorganisms and identify the present of Staphylococcus aureus (S. aureus) inside the cattle farm. DRF e-MAS which was owned prepared by Arduino kit had been used to observe the microorganisms’ population.The air from surrounding that contained microorganisms being aspirated into the plate chamber of the DRF e-MAS. The nutrient agar that being placed inside the plate chamber will be incubated along with aspirated microorganisms and the result of microorganisms’ population will be observed. S. aureus is one of the possible bacteria that may be found among the population of the microorganisms in cattle farm. DRF e-MAS along with Baird Parker Agar being used to identify the present of S. aureus. Baird Parker Agar is used to enhance the growth of S. aureus while eliminating the others. After being incubated, a single colony of S. aureus that grew on the Baird Parker Agar had been picked and regrow on another nutrient agar. A single colony that formed on that nutrient agar will be picked and then undergo Coagulase test and IMViC test. Coagulase test involved the citrated plasma and the present of bubbles show positive result. On the other hand, IMViC test divided into four sub-test which are Indole test, Methyl red test, Voges-Proskauer test and Citrate test. These tests are important in order to confirm the present of S. aureus in this farm. According to the test, there was S. aureus found among the microorganisms’ population inside this barn.